Knowledge, attitude, and practice towards COVID-19; A community survey in North-Borneo (Sabah), Malaysia - S.Z.S.A. Yunus; M.H. Mohamed; M.A.M. Fauzi; G. Marimuthu; M.F.M. Anuar; N. Ithnain; S.S.S.A. Rahim (Tarbiat Modares University, 2022)
Aims: The COVID-19 pandemic has severely impacted the global economy as well as the healthcare delivery systems. Without effective treatment and vaccines in the earlier phase of the pandemic, the public needs to engage in precautionary behaviors and disease surveillance and response at the policy level. This study aimed to describe the knowledge, attitude, and practice toward COVID-19 among the residents in Sabah, Malaysia. Instruments & Methods: An online cross-sectional study was conducted using convenience sampling from March to April 2020. The chi-square test and multiple logistic regression were used to examine the association factors of knowledge, attitude, and practice towards the COVID-19 pandemic. Findings: A total of 536 participants completed the questionnaire. The mean knowledge score was 10.1±1.2, and 84.2% had a correct rate of knowledge. The attitude towards the final success in controlling COVID-19 was significantly different in age groups, marital status, and occupation types (p<0.05). Those with higher knowledge scores were more likely to agree with the confidence of the final success in controlling COVID-19. 94.4% were confident that Malaysia will win the battle against the COVID-19 pandemic. People in government sectors were 6.19 times more likely to wear masks than unemployed respondents. Conclusion: The level of knowledge of the residents in Sabah, Malaysia, about COVID-19 is quite satisfactory. Meanwhile, attitudes and practices towards COVID-19 differ according to the socio-demography of the population in Sabah..